Two-Component Signal Transduction Systems: A Major Strategy for Connecting Input Stimuli to Biofilm Formation - Liu, Cong; Sun, Di; Zhu, Jingrong; Liu, Weijie (Frontiers in Microbiology, 2019)
Biofilms are multicellular communities of microbes that are encased within an extracellular matrix. Environmental factors induce the biofilm formation of bacteria. Bacteria have several regulatory mechanisms in response to environmental changes, and the two-component signal transduction system (TCS) is a major strategy in connecting changes in input signals to changes in cellular physiological output. The TCS employs multiple mechanisms, such as cross-regulation, to integrate and coordinate various input stimuli with regulation of biofilm formation. In this mini-review, we demonstrate the roles of TCS on biofilm formation, illustrating these input signals and modulation modes, which may be utilized by future investigations in elucidating the regulatory signals and underlying mechanisms of biofilm formation.